2020
DOI: 10.1109/tmi.2019.2933813
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Aggregate Cardiomyocyte Strain Using $In~Vivo$ Diffusion and Displacement Encoded MRI

Abstract: Changes in left ventricular (LV) aggregate cardiomyocyte orientation and deformation underlie cardiac function and dysfunction. As such, in vivo aggregate cardiomyocyte "myofiber" strain (E ff ) has mechanistic significance, but currently there exists no established technique to measure in vivo E ff . [1] The objective of this work is to describe and validate a pipeline to compute in vivo E ff from magnetic resonance imaging (MRI) data. Our pipeline integrates LV motion from multi-slice Displacement Encoded wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…McGowan et al 37 found a similar strain (E ff = −0.14 ± 0.01) while Wang et al 13 found a higher magnitude (E ff = −0.18 ± 0.03), using both MRI tagging imaging and ex vivo myofiber orientations. Very similar results were found in our previous work 15 in healthy swine (E ff = −0.14 [−0.16, −0.14]) using in vivo cDTI and 3D displacement encoded DENSE. Slightly lower E ff magnitudes were obtained in healthy human in vivo (E ff = −0.13 ± 0.02) using a single DENSE slice with an imposed incompressibility constraint 14 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…McGowan et al 37 found a similar strain (E ff = −0.14 ± 0.01) while Wang et al 13 found a higher magnitude (E ff = −0.18 ± 0.03), using both MRI tagging imaging and ex vivo myofiber orientations. Very similar results were found in our previous work 15 in healthy swine (E ff = −0.14 [−0.16, −0.14]) using in vivo cDTI and 3D displacement encoded DENSE. Slightly lower E ff magnitudes were obtained in healthy human in vivo (E ff = −0.13 ± 0.02) using a single DENSE slice with an imposed incompressibility constraint 14 …”
Section: Discussionsupporting
confidence: 90%
“…The proposed post-processing approach to combine cDTI and DENSE is in continuity of the study done by Verzhbinsky et al 15 In this previous study, two SA slices of 3D displacement encoding DENSE were acquired immediately above and below one SA cDTI to estimate E ff . In this work instead, a stack of 2D SA and LA DENSE slices were combined with the cDTI data.…”
Section: Combination Of Cdti and Dense Acquisitionsmentioning
confidence: 93%
See 2 more Smart Citations
“…1 ) comprised of the following steps: (a) LV segmentation, (b) identification of the anterior RV-LV insertion point, (c) phase unwrapping, and (d) displacement and strain analysis. Steps (a)–(c) utilize CNNs, and step (d) uses previously-developed and validated fully-automatic methods [ 5 , 31 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%